(untitled) (Castilla. Estudios de Literatura, 2018)
Abstract: When Lorca decided to publish Poeta en Nueva York, in 1936, he conceived the book as a dialogue between verbal images and visual images. The Mexican edition, however, had only four drawings and no photographs. This work wants to verify what is lost when the photographs are lost. Lorca left us enough evidence to reconstruct the original project that his murder cut off. Photographs are an essential part of this. It means a rejection of any explanation of the photos as illustrations or as simple support of the texts. In fact, they resist any intention to order them that way. They interact with words in a dynamic way, altering them, modifying them or giving them new nuances and meanings. That is, without doubt, the value that Lorca gave them, because his plastic sensibility discovered in New York the central place of visual images in Modernity.